EFFECT OF LABOR PRODUCTIVITY ON POVERTY IN WEST KALIMANTAN - Firman, Firman Tiro; Bariyah, Nurul; Kurniasih, Erni Panca (Jurnal Ekonomi Pembangunan, 2019)
The purpose of this study was to determine the effect of labor productivity on poverty, economic growth and GDP per capita in West Kalimantan, and to determine the effect of economic growth and GDP per capita on poverty in West Kalimantan. The variables used are poverty level, labor productivity, economic growth and GDP per capita of 14 districts / cities in West Kalimantan from 2008-2017 sourced from the Central Statistics Agency of West Kalimantan. Analysis used by using path analysis. The results show that labor productivity has a negative and significant effect on poverty. Labor productivity partially has a positive and significant effect on economic growth and GDP per capita, while economic growth and GDP per capita have no partial effect on poverty, and a greater direct effect on labor productivity on poverty in West Kalimantan than indirect effects either through economic growth and GDP per capita.